Cost-effectiveness analysis of sintilimab vs. placebo in combination with chemotherapy as first-line therapy for local advanced or metastatic oesophageal squamous cell carcinoma - Shao, Taihang; Zhao, Mingye; Tang, Wenxi (Frontiers in Oncology, 2022)
Objective: Results of Orient 15 indicated the health benefits to patients with local advanced or metastatic oesophageal squamous cell carcinoma (OSCC). This study aimed to evaluate the cost-effectiveness of sintilimab plus chemotherapy in treating OSCC from the perspective of Chinese healthcare system. Methods: A partitioned survival model was constructed to evaluate the cost-effectiveness of sintilimab plus chemotherapy vs. chemotherapy in treating OSCC. Baseline characteristics of patients and key clinical data were extracted from Orient 15. Costs and utilities were collected from published studies and open-access databases. Costs, quality-adjusted life-years (QALYs), life-years gained, and incremental cost-effectiveness ratios (ICER) were chosen as economic outcome indicators. We also performed sensitivity analyses and subgroup analyses to verify the stability of results. Results: Combination therapy provided additional 0.84 QALYs and 1.46 life-years with an incremental cost of $25,565.48 than chemotherapy, which had an ICER of $30,409.44 per QALY. The probabilistic sensitivity analysis indicated that combination therapy had a 98.8% probability of cost-effectiveness at the willingness-to-pay threshold (WTP) of $38,184 per QALY. Deterministic sensitivity analysis showed that model outcomes were sensitive to the utilities of progression-free survival and progression disease. The subgroup analysis revealed that combination therapy was cost-effective in patients with high expression of PD-L1 and several specific subgroups. Conclusion: In this economic evaluation, sintilimab plus chemotherapy was likely to be cost-effective compared with chemotherapy in the first-line therapy of advanced OSCC from the perspective of Chinese healthcare system. Our findings may provide evidence for clinicians to make optimal decisions in clinical practice and for decision-makers to evaluate the cost-effectiveness of sintilimab.